Problems and dilemas in applying different techniques in fish population dynamics studies - Jukic-Peladic S.; Vrgoc N. (Dynamique des populations marines, 1998)
Estimates of mortality coefficients (natural, fishing and total) for three species, Silver Hake (Merluccius merluccius L.), Striped Mullet (Mullus barbatus L.) and Pandora (Pagellus erythrinus L.) of the Adriatic Sea have been obtained by several procedures. Two methods of analysis of normal components of the frequency distributions and Pauly's formula, relating mortality with growth and temperature, have been applied to data collected during 1948-1949 in the 'HVAR' cruise in the Adriatic Sea, where for many years because of the Second World War, there had not been trawl fishing. For that reason, the virgin state for the sampled populations could be assumed.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)